The evolution of the juvenile court: race, politics, and the criminalizing of juvenile justice - Feld, Barry C. (Youth, crime, and justice series, 2017)
The progressive juvenile court -- The due process revolution and the juvenile court -- The get tough era I : structural change and youth crime -- The get tough era II : politics of race and crime -- The kid is a criminal : transfer and delinquency sanctions -- The girl is a criminal : the impact of get tough policies on girls -- The student is a criminal : get tough policies and the school-to-prison pipeline -- The criminal is a kid : adolescents' diminished culpability -- The defendant is a kid : adolescents' competence to exercise procedural rights -- Epilogue : opportunities and obstacles